تطبيق وسيلة بطاقات الأسئلة والأجوبة في تعليم مهارة القراءة لتنمية التحصيل الدراسي عند الطلاب - Mustakim, Nyak; Saputra, Riski (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2021)
The purpose of this study is to explain the students’ responses and to measure the effectiveness of the use of question and answer card media on student learning outcome in qiraah learning at Daru Al-Saa'dah Islamic boarding school. The research method used is experimental research with a two-group design, namely the experimental group in the form of question and answer card media treatment and the control group that is not treated in the form of question and answer card media, The instrument used to collect data in the form of qiraah test questions given to the group experimental and control groups. The results showed that the use of question and answer card media was effective in improving the ability of Daru Al-Saa'dah students in reading skills, this was evident from the results of the t-test by using SPSS programs where the t-count value showed a number greater than the t-table.